ANALYSIS OF PROBABILISTIC BASED GUIDANCE ALGORITHM USING GAME THEORY APPROACH - DEWANGGA , WISNU
In the modern era, missiles have been used to serve both defense and offense purposes. Despite various details surrounding each missile, they can be categorized into two major groups based on their assigned motion or maneuvers during missions, guided and unguided. A guided missile system comes with a guidance package that manipulates the missile, forcing it to stay within its’ course up to its’ collision with the desired target. Numerous research projects have been conducted to improve various aspects of missile systems, particularly the guidance system since this feature had been proven to relieve missile users of several workloads related to monitoring and control issues during a missile’s mission.